Síntese e caracterização de líquidos iônicos próticos combase catiônica 2-hidroxi trietilamônio: solubilidade decorantes têxteis - Moraes, Maria Renata (2013)
In Brazil the textile sector has a great importance, and has been concerning increasingly with the conservation of hydrous resources, because are spent in average 100 liters of water for each kilo of fabric to dye. Because of this oncern with hydrous resources the referring research aimed the synthesis of protic ionic liquids from the cationic base 2-hydroxy triethylammonium 2 (HTEA) varying the anionic base: A-acetate, Pr-propionate, B-butanoate and Pe-pentanoate which resulted in 4 syntheses. The PILs synthesized were used to the study of measurements of solubility of three dyes classes (acid, dispersed and reactive) analyzed in the temperatures of 40 ºC, 50 ºC, 60 ºC, 70 ºC and 80 ºC. The measurements of solubility of the three dyes classes in the PILs (performed on a spectrophotometer UV-VIS) had as guiding principle the substitution of water, which is the liquid environment most used by the textile industry to the solubilization of textiles dyes, by the PILs synthesized in this work. During the research was realized the chemical identification of the PILs through the nuclear magnetic resonance (NMR) technique which verifies the structure of the ionic salt. It was analyzed: water content, the thermic analysis (thermogravimetry/TG and differential scanning calorimetry/DSC), ionic conductivity, density and viscosity. The results achieved by many authors regarding the analysis mentioned above pointed the same behavior by the characteristics of some PILs. It was identified a trend of results with the decrease of viscosity and density with the temperature increase, the opposite was observed in the analysis of ionic conductivity and the measures of the solubility of textiles dyes in the PILs. Based on the experimental results, the simplicity of synthesis, low coast, the possibility of reutilization (recycling) and the results of solubility of the textile dyes in the PILs studied, is concluded that the substitution of water by the PILs in the solubilization of dyes in the textile industry has a very promising potential, including the substitution in the textile dyeing process